Questionnaire Survey on the Current Situation and Experience in Prevention and Control Measures at Urology Clinics During the COVID-19 Epidemic in China - Zhu, Xiao-Liang; Jiang, Hai-Hong; Jiang, Ming-Hui; Liu, Wen-Li; Sheng, Zi-Lu; Liu, Jia-Hui; Wang, Meihao (Frontiers in Public Health, 2021)
Abstract Purpose: Although the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2, has been viably controlled in China, a new normal in healthcare strategies has become standard in China and worldwide. We conducted a questionnaire study to disseminate the experience from China in terms of urology outpatient prevention and control measures under standardized prevention policies against COVID-19. Participants and methods: From May 3, 2020 to June 25, 2020, we conducted an anonymous cross-sectional questionnaire study, focused on the status of and experiences with outpatient urology prevention and control measures during the COVID-19 pandemic. The targeted respondents were urologists in mainland China, covering all levels of hospitals and clinics. Results: A total of 216 (97%) valid responses were collected. We found that 183 (85%) respondents were from outside of Hubei province in China. One-hundred-and-fifty-eight (73%) respondents believed that SARS-CoV-2 could be detected in urine, and that protection against urine exposure was needed. Over 80% of respondents recommended WeChat application or similar online video meetings for virtual outpatient consultations. The suggested flowcharts and recommendations to prevent new cases were easy to understand and approved by most physicians, which could provide reference for outpatient prevention and control. We still need to make adequate preparations under the new normal of the COVID-19 Epidemic, especially for those suspected of being infected. Conclusions: Although the scientific validation of the questionnaire is limited, it provides a first snapshot of the experiences relating to the prevention and control measures in urology clinics in China, and can inform future policies in this field.